2014
DOI: 10.17221/7289-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Composition of major proteins in cow milk differing in mean protein concentration during the first 155 days of lactation and the influence of season as well as short-term restricted feeding in early and mid-lactation

Abstract: A variety of proteins contributes greatly to the unique nutritional and functional quality of dairy cow milk. Particularly, milk casein content and composition have substantial influence on the processing capabilities. In the present study, milk of 23 multiparous Holstein-Friesian cows, grouped as high-(3.49 ± 0.05%; n = 11) and low-protein (3.03 ± 0.05%; n = 12) cows, was sampled approximately weekly during the first 155 days of lactation to determine the course of relative milk protein composition (α-lactalb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 30 publications
4
31
0
3
Order By: Relevance
“…These results confirm those obtained by Bernabucci et al (2002) in a research carried out on dairy cows monitored in spring and summer in a commercial dairy herd in Central Italy, in this case the concentration of protein fractions was measured by electrophoresis on cellulose acetate. Gellrich et al (2014) recently observed seasonal effect on α-CN and β-CN, with higher β-CN as a percentage of protein in summer season. In this last paper, major milk protein analyses were conducted using a microfluidic electrophoresis and no data were presented on climatic condi-tions; thus it is not possible to adequately compare the present with the Gellrich et al study.…”
Section: Cn Fractionsmentioning
confidence: 92%
See 1 more Smart Citation
“…These results confirm those obtained by Bernabucci et al (2002) in a research carried out on dairy cows monitored in spring and summer in a commercial dairy herd in Central Italy, in this case the concentration of protein fractions was measured by electrophoresis on cellulose acetate. Gellrich et al (2014) recently observed seasonal effect on α-CN and β-CN, with higher β-CN as a percentage of protein in summer season. In this last paper, major milk protein analyses were conducted using a microfluidic electrophoresis and no data were presented on climatic condi-tions; thus it is not possible to adequately compare the present with the Gellrich et al study.…”
Section: Cn Fractionsmentioning
confidence: 92%
“…Bernabucci et al (2002) did not observe any difference for α-LA and β-LG between seasons. Gellrich et al (2014), in a research carried out in Germany studying the effect of season, observed greater α-LA concentration in summer compared with the fall season. Similarly, Brodziak et al (2012) found a significantly higher concentration of α-LA and a higher ratio of α-CN:β-CN in milk of cows from the spring-summer season, in comparison with the fall-winter period.…”
Section: Whey and Serum Protein Fractionsmentioning
confidence: 93%
“…Milk production increases in early lactation (Szencziová et al 2013) and despite simultaneously increased feed intake, the cow's metabolism goes through the negative energy balance (NEB) phase of lactation (Kadlecová et al 2014b). This standard course of the postpartum period of all dairy cows evokes body fat reserve degradation as an additional source of energy, concurrently followed by a decline in live weight (Řehák et al 2012), body condition score (BCS) (Stádník et al 2002;Ducháček et al 2012a) causing a simultaneous decrease of reproduction (Louda & Stádník 2000;Ducháček et al 2012b) and impairment of health (Vacek et al 2007), and/or changes in milk composition (Gellrich et al 2014). Lipomobilisation increases free fatty acid plasma content and triacylglycerol accumulation in the liver tissue affecting its structure and function (Shibano & Kawamura 2006;Jóźwik et al 2012).…”
mentioning
confidence: 99%
“…Casein, a major phosphoprotein found in milk is composed of several casein fractions that are distinguished by electrophoresis and are designated as α-, β-, and k-caseins (in order of decreasing mobility at pH 7.0). In bovine milk, casein composition, in mg mL −1 , consists approximately as follows: αs 1 (12)(13)(14)(15); αs 2 (3)(4); β (9-11); and k (2)(3)(4) [1,2]. These fractions vary in molecular weight, isoelectric point, and level of phosphorylation.…”
Section: Milk Structurementioning
confidence: 99%
“…In cow milk, for example, the protein composition during seasons vary between 33.8-34.8, 31.2-32.6, 15.5-16.2, 2.0-2.1, 9.6-9.9, and 5.6-6.5 g protein/100 g total protein for α-, β-, and kcasein, α-lactalbumin, β-lactoglobuin, and other proteins (e.g. bovine serum albumin and lactoferrin) [4].…”
Section: Milk Structurementioning
confidence: 99%